Representações discursivas de Ficar e Namorar em textos de vestibulandos e pré-vestibulandos - Ramos, Milton Guilherme (2011)
This doctoral thesis investigate the way vestibulandos and pré-vestibulandos construct their discursive representations of Ficar and Namorar in their textual production. At the same time, aims to discuss its implications for the ATD and for the teaching and learning of textual production in the context of Portuguese Language classes. Its theoretical framework is inspired mainly by three sources: textual linguistics, the textual analysis of discourses (ADAM, 2008), as well as by frames semantics (FILLMORE, 2006; FELTES, 2007). The methodology is based on a combination of qualitative and quantitative approaches (VIANNA et al., 2008). The data is composed of 168 empirical texts written by the vestibulandos of PSV/2005 da UFRN, Natal, RN, and by secondary school students who attended Escola Estadual Juscelino Kubitschek (EEJK), Assú, in the 2008 school year. The results indicate different categories of discursive representations of Ficar and Namorar , such as designation of referents, prediction, aspectualization, spatial-temporal circunstances , and metaphor, which reveal the influence of factors such as: the encyclopedic knowledge, the culture, as well as the cognitive components related to textual production. These results point out to the necessity of a teaching practice which enables the interaction among students, the discussion of current themes, as well as the student involvement with different textual genres, mainly the work with textual production in the classroom, so that it enables the students do acquire the textual production strategies. Thus, the overall goal is the (re)construction of their discursive representations, so that they can cope with new contexts of communicative interaction.